Fto-modulated lipid niche regulates adult neurogenesis through modulating adenosine metabolism. (7th August 2020) - Gao, Hui; Cheng, Xuejun; Chen, Junchen; Ji, Chai; Guo, Hongfeng; Qu, Wenzheng; Dong, Xiaoxue; Chen, Yingyan; Ma, Linghan; Shu, Qiang; Li, Xuekun
Abstract: Adult neurogenesis is regulated by diverse factors including the local environment, i.e. the neurogenic niche. However, whether the lipid in the brain regulates adult neurogenesis and related mechanisms remains largely unknown. In the present study, we found that lipid accumulates in the brain during postnatal neuronal development. Conditional knockout of Fto (cKO) in lipid not only reduced the level of lipid in the brain but also impaired the learning and memory of mice. In addition, Fto deficiency in lipid did not affect the proliferation of adult neural stem cells (aNSCs), but it did inhibit adult neurogenesis by inducing cell apoptosis. Mechanistically, specific deleting Fto in lipid altered gene expression and increased adenosine secretion of adipocytes. The treatment of adenosine promoted the apoptosis of newborn neurons. As a whole, these results reveal the important function of the lipid niche and its associated mechanism in regulating adult neurogenesis.